KETAHANAN DAN KEHARMONISAN KELUARGA DALAM PERBEDAAN PILIHAN POLITIK MENURUT TAFSIR AL-MISHBAH DAN TAFSIR AL-AZHAR - marsila sila; Eka Febriyanti; Islamiyah Islamiyah (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
Differences in political choices are one of the causes of conflict in the family, which can even reach the stage of abuse and divorce between husband and wife. As happened in Batu Aji, Batam. This article aims to describe and analyze differences in political choices that result in conflict and violence. This article is the result of library research and data analysis from various sources. The result of this writing is about maintaining family resilience and harmony despite differences in political choices, namely by understanding and respecting each other. Then try to consult each other when faced with a problem. The Qur'an as a guide to life for mankind certainly provides many solutions to every problem. Including in this case, the author tries to understand and find ease in interpreting solutions to the content of the Al-Qur'an from the existing tafsir books.